2019
DOI: 10.21037/qims.2018.10.13
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific 3D printed pulmonary artery model with simulation of peripheral pulmonary embolism for developing optimal computed tomography pulmonary angiography protocols

Abstract: Background: Computed tomography pulmonary angiography (CTPA) is the preferred imaging modality for diagnosis of patients with suspected pulmonary embolism (PE). Radiation dose associated with CTPA has been significantly reduced due to the use of dose-reduction strategies, however, investigation of low-dose CTPA with use of different kVp and pitch values has not been systematically studied. The aim of this study was to utilize a 3D printed pulmonary model with simulation of small thrombus in the pulmonary arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…Patient-specific 3D-printed models based on patient's imaging data offer realistic models with a high accuracy in replicating anatomy and pathology, thus serving as a reliable tool to optimize CT protocols. Currently, 3D-printed heart and pulmonary artery models have been used to test different CT scanning protocols for dose optimization (47)(48)(49). The 3D-printed cardiac insert phantom developed by Abdullah et al represents a novel approach for optimizing cardiac CT protocols (48), while 3D-printed pulmonary artery model by Aldosari et al indicates another new approach for optimizing CT pulmonary angiography protocols with simulation of main and peripheral pulmonary embolism ( Figure 5).…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-specific 3D-printed models based on patient's imaging data offer realistic models with a high accuracy in replicating anatomy and pathology, thus serving as a reliable tool to optimize CT protocols. Currently, 3D-printed heart and pulmonary artery models have been used to test different CT scanning protocols for dose optimization (47)(48)(49). The 3D-printed cardiac insert phantom developed by Abdullah et al represents a novel approach for optimizing cardiac CT protocols (48), while 3D-printed pulmonary artery model by Aldosari et al indicates another new approach for optimizing CT pulmonary angiography protocols with simulation of main and peripheral pulmonary embolism ( Figure 5).…”
Section: A B C Dmentioning
confidence: 99%
“…The 3D-printed cardiac insert phantom developed by Abdullah et al represents a novel approach for optimizing cardiac CT protocols (48), while 3D-printed pulmonary artery model by Aldosari et al indicates another new approach for optimizing CT pulmonary angiography protocols with simulation of main and peripheral pulmonary embolism ( Figure 5). Significant dose reduction up to 80% can be achieved with resulting diagnostic images of detecting pulmonary embolism at the main and peripheral pulmonary arteries, thus highlighting the feasibility of using 3D-printed pulmonary model for developing low-dose CT protocols (48,49).…”
Section: A B C Dmentioning
confidence: 99%
“…Of 8 original articles, 4 focused on the usefulness of 3D printing in cardiovascular disease with 2 of them studying the optimal computed tomography pulmonary angiography (CTPA) protocols based on their developed 3D printed pulmonary artery model (15,16). Pulmonary embolism was simulated by inserting the animal blood clots in the main pulmonary arteries with CTPA scans performed on the 2 nd generation of dual-source CT scanners (15).…”
mentioning
confidence: 99%
“…Dose reduction up to 80% was achieved when lowering kVp from 120 to 100 or 80 without significantly affecting image quality in detecting main pulmonary embolism, while use of 70 kVp and high pitch of 3.2 was not recommended due to suboptimal image quality when CT scans were done a 128-slice dualsource CT. However, in the subsequent experiments of simulating peripheral pulmonary embolism using the same approach, authors tested the same CTPA protocols on the latest 192-slice 3 rd generation dual-source CT scanner with images reconstructed using advanced modelled iterative reconstruction (ADMIRE) (16). Both qualitative and quantitative assessments of image quality showed that lowdose CTPA is achievable with use of 70 kVp and high pitch of 2.2 or 3.2, with significant dose reduction while still maintaining diagnostic images of detecting small emboli in the pulmonary arteries.…”
mentioning
confidence: 99%
“…An increasing trend in research and publications have been observed recently in the journal of Quantitative Imaging in Medicine and Surgery (QIMS), especially in the 2019 January special issue with a focus on 3D printing in medicine. In that special issue, a number of publications (original studies, technical notes and review articles) were contributed by researchers from different countries with expertise in different fields highlighting the importance of 3D printing in medical applications (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). In addition to these applications, a recent paper in this issue of QIMS presents another new research direction of using personalized 3D printed coronary artery models for simulation of coronary stenting procedure (14).…”
mentioning
confidence: 99%